(untitled) (Journal of Governance and Development (JGD), 2015)
As people of Uganda’s Acholi sub region struggle to rebuild their livelihoods after more than two decades of armed insurgency and internal displacement, they remain suspicious of the government’s motive to allocate their land to foreign investors. By taking Amuru District Land Board to court for allocating their land to Madhvani Group’s Amuru Sugar Works in 2007, the local community has underlined its distrust of the government and its institutions. They hold that the idea of promoting large scale agro-based industrial production through Madhvani sugar project was a falsehood and that Madhvani was merely a smokescreen to disguise land grabbing by big people in government. The findings of this study highlight deep suspicion of government motive in allocating 1,200 hectares of land in Amuru district to Madhvani Group which, to them, strongly revives the historical perception of marginalisation of northerners (who include the Acholi). The conclusion from the study is that although international capital is vital for the recovery process, where it involves natural resources such as land, its effectiveness is likely to be affected negatively unless local communities are included in the planning process; which calls for an inclusive rather than a top-down recovery strategy.